Optimalisasi Pelayanan Publik dalam Pengelolaan Pendapatan Daerah di Kantor Badan Pendapatan Daerah Kabupaten Padang Lawas - Hasibuan, Maisyah Khairani; Soemitra, Andri (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2024)
Optimal public services in managing local revenue are key to the success of a region in building self-reliance and the welfare of its people. This research aims to investigate efforts to optimize public services in managing local revenue at the Office of the Regional Revenue Agency of Padang Lawas Regency. The research method used is qualitative with data collection techniques through in-depth interviews, observation, and documentation study. The results show that there are several factors influencing the optimization of public services at the Office of the Regional Revenue Agency of Padang Lawas Regency, including policy factors, human resources, and information technology. Additionally, various strategies were found that can be implemented to improve public services in managing local revenue, such as enhancing training and development of human resources, improving information accessibility, and enhancing coordination among units within the agency.